2017
DOI: 10.1007/s10597-017-0112-0
|View full text |Cite
|
Sign up to set email alerts
|

Dimension and Socio-demographic Correlates of Domestic Violence: A study from Northeast India

Abstract: Present study was aimed to find out dimension and socio-demographic correlates of domestic violence in Assam, Sikkim and Meghalaya, Northeast India. Two districts from each state were selected at random and women aged 18-35 years from rural and urban localities were interviewed to obtain relevant information. The study included a total of 2249 participants (Rural = 1577 and Urban = 672) from Assam (650), Sikkim (1148) and Meghalaya (451). Domestic violence was recorded in 26.4% of study participants and highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
6
1
Order By: Relevance
“…According to the results of NFHS-3 multiple risk factors similar to our study results were found to be associated with Domestic violence; namely educational attainment by the female, her employment status, the employment status of the husband, alcohol consumption by the partner and demographic factors like caste and religion. 21 Similar to our study results, independent variables for gender-based violence found in a study done by Ngonga in Zambia are; alcohol abuse, income level, area of residence and gender. 24 Study by Semahegn found that alcohol consumption by husband, being pregnant, decision making power and annual income to be predictors of domestic violence in Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…According to the results of NFHS-3 multiple risk factors similar to our study results were found to be associated with Domestic violence; namely educational attainment by the female, her employment status, the employment status of the husband, alcohol consumption by the partner and demographic factors like caste and religion. 21 Similar to our study results, independent variables for gender-based violence found in a study done by Ngonga in Zambia are; alcohol abuse, income level, area of residence and gender. 24 Study by Semahegn found that alcohol consumption by husband, being pregnant, decision making power and annual income to be predictors of domestic violence in Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
“…In NFHS -3 report shows that lifetime sexual violence was 9% of sample of 69704 ever-married women between the ages 15 to 49 who participated. 21 Study done in Pondicherry by George et al reported sexual violence against 13.5% of 310 participants in their study, which is much higher than our study reports. 26 Study done in Saudi Arabia by Barnawi found that violence against women ranged from being emotional (69%), social (34%), economic (26%), physical (20%), and sexual violence (10%).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Studies have reported about the prevalence of IPV among women with low socio-economic and demographic profiles such as urban residence, lower education, and lower family income. 6,13,[22][23][24][25][26][27] The majority of them were housewives and financially dependent upon husbands which put them under the risk of violence. In-laws' interferences, decision-making process by husband and other family members and less time spent with each were factors contributed to DV.…”
Section: Discussionmentioning
confidence: 99%